Investigation of diaphragmatic and deep abdominal muscle function in patients with ankylosing spondylitis and its relationship with clinical parameters: An ultrasound-based study - Ugur Verep; Tuba Demirci Yildirim; Ozkan Urak; Fatos Onen; Ismail Sari; Seher Ozyurek (Journal of Back and Musculoskeletal Rehabilitation, 2026)
Purpose This study aimed to evaluate differences in diaphragm and deep abdominal muscle function between patients with ankylosing spondylitis (AS) and healthy controls and to examine their relationships with clinical parameters, including spinal mobility, quality of life, and balance performance. Materials and Methods Patients with AS and healthy controls were included. Diaphragm and deep abdominal muscles were evaluated using two-dimensional ultrasonography. The clinical status of AS patients was assessed using ASDAS, BASDAI, BASFI, BASMI, and ASQoL. Static and dynamic balance were assessed with the NeuroCom Balance Master, including limits of stability (LOS) and sit-to-stand (STS) tests. Results 30 AS patients (27 male, 3 female) and 33 healthy controls (27 male, 6 female) were assessed. Ultrasound measurements showed significant between-group differences in diaphragm thickness at end-expiration (p = 0.021), transversus abdominis (TrA) thickness at rest (p = 0.009), and TrA thickening fraction during the abdominal drawing-in maneuver (p = 0.010). AS patients demonstrated lower scores in several LOS and STS parameters compared with controls (p < 0.05). A significant negative correlation was found between the thickening fraction of the internal oblique muscle (TF IO ) and ASQoL (r = −0.371, p < 0.05). TF IO showed positive correlations with BASMI (r = 0.439, p < 0.05) and tragus-to-wall distance (r = 0.461, p < 0.05). For the internal oblique muscle, resting thickness correlated positively with cervical rotation (r = 0.464, p < 0.01), while TF IO correlated negatively with cervical rotation (r = −0.571, p < 0.01). Conclusion AS patients exhibit greater diaphragm end-expiratory thickness and resting TrA thickness than controls; however, reduced TrA thickening fraction indicates functional impairment despite these structural changes.